RELASI MASYARAKAT MARGINAL SEBAGAI LIYAN DALAM KONFLIK AGRARIA DI INDONESIA DALAM PERSPEKTIF LIYAN SEBAGAI ORANG KETIGA ARMADA RIYANTO - Rex Firenze Tonta (Institut Agama Kristen Negeri Toraja, 2023)
This article aims to identify patterns of relations between marginalized communities (indigenous communities, farmers, etc.) and the state (government, regulations, officials) in agrarian conflicts in Indonesia. This article uses Armada Riyanto's thinking about